Penentuan Interval Perawatan Mesin Wood Pallet Secara Preventif Dengan Metode Modularity Design Dan Age Repalcement Pada PT Yale Woodpallet Indonesia - Shesfi Nur Hidayah; Endang Pudji Widjajati (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2023)
In an effort to increase productivity to ensure smooth production processes, it is necessary to implement an appropriate maintenance system to reduce production machine downtime. The purpose of company maintenance is to keep production machines in good condition so that production operations can run efficiently and effectively. PT Yale Woodpallet Indonesia is a company in Indonesia that produces wooden pallets (wood pallet). This company often experiences problems with damage to machines due to suboptimal machine maintenance because the maintenance system is carried out to repair damaged components with new components resulting in downtime. Among these problems, this study aims to determine maintenance intervals to minimize maintenance costs by using modularity design and age replacement methods. Based on the analysis of the results obtained, it is known that the modularity design and age replacement methods can achieve optimal component replacement intervals for pallet machine components is 30,000 minutes, rotary screening components are 33,200 minutes and hopper components are 33,200 minutes. The total maintenance cost per year is Rp. 2,115,610,959, -. compared to the company's maintenance costs which have a value of Rp. 2,668,692,000, the maintenance system using the modularity design and age replacement method is more efficient by 1.27%.